`I`m just doing it because it`s what the club wants`: exploring the (mis)alignment between policy compliance and preferred practice among English football youth academy coaches - Aderiye, F.; Mulvenna, C.; Lusted, J. (Sports Coaching Review, 2026)
This article explores the various ways that coaches receive and enact policy-informed organisational expectations of practice. Semi-structured interviews were undertaken with 14 male English football academy coaches to explore their experiences of aligning practice to broader policy-led goals. Goffman`s dramaturgy theory (1959) is used to frame these experiences, with policy compliance often prompting impression management "performances" of practice. Findings suggest that the process of adopting the "role" of a policy compliant coach can cause varying degrees of misalignment between a coach`s expected practice and how they prefer to coach. This in turn shapes the extent to which coaches feel compelled to "fabricate" their practice. The paper advocates for greater recognition of how policy can shape coaching practice in varied ways. Policy makers should consider the consequences that may arise from a misalignment between a coach`s preferred practice and that which is expected of them when performing policy compliance.